THE ROLE OF CU ELEMENT AND COMPACTION PRESSURE ON MICROSTRUCTURE AND MECHANICAL PROPERTIES OF AL-CU BINARY ALLOY SYNTHESIZED BY POWDER METALLURGY - Suprianto; Muhammad Ramadhan; Almi Syafroza; Farida Ariani (DINAMIS, 2023)
Al-Cu alloys are promising material for engineering field due to their good mechanical properties. These characteristics could be obtained by addition of some elements and correct selected processes parameter. The purposes of this current study to investigate the effect of Cu contents and compaction pressure on microstructure evolution and mechanical properties of the Al-Cu alloy synthesized by powder metallurgy route. High purity Al and Cu elements are used as starting material with composition (21.0, 24.0, 27.0, 30.0, and 33.0) wt.%Cu with 210 MPa of compaction pressure. The varying compaction pressure 160, 180 and 180 MPa were carried for 15 minute holding time. Furthermore, a conventional sintering at 500oC for 1 hour holding time take place. The hardness test resulted that the increases of Cu contents was successfully improved the hardness, which is the maximum hardness 53.2 HV and 71.47 MPa of the compressive strength obtained by 33wt. Cu addition. On the other hand, the varying of compaction pressure resulted the maximum hardness and compressive strength are 25.6 HV and 60.8 MPa respectively for 200 MPa. The microstructure observation shows the increases of Cu promoted more Cu elements dispersed between the aluminum rinh matrix. The increase of compressive strength is encourages finer Al-Cu grain in the microstructure.